KONTRIBUSI KEKUATAN OTOT PERUT TERHADAP KEMAMPUAN HEADING PEMAIN SEPAKBOLA CAHAYA MOTOR FC - Amriusman Ndruru; Cundra Bahar; Roki Putra (EDU RESEARCH, 2023)
Based on the researcher's monitoring of the phenomena that occur in the field, the researcher suspects that the abdominal muscle strength of Cahaya Motor FC Padang football players is still far from expected, this is evident from: the strength of the player in heading the ball is weak, the ball that is headed is not on target and does not arrive at the destination. The purpose of this research is "to find out how much there is a contribution between abdominal muscle strength to the heading ability of Cahaya Motor FC Padang players". In this study, the population is Cahaya Motor FC Padang players who are still actively training and registered as Cahaya Motor FC Padang players in 2023, totalling 30 people. Guided by the research population, the sample in this study is all the existing population, namely Cahaya Motor FC Padang players who are still actively training and registered as Cahaya Motor FC Padang players in 2010, totalling 30 people. Before testing the hypothesis, the data analysis requirements were tested with the data normality test (Lilliefors test) at a significant 0.05. Then after that because the different test tools cause the number of digits in the data to be different so that it must be converted into T-Score form using the T-Score formula from Don R Kirkendall. Based on the results of the study, it can be concluded that "There is a Contribution Between Abdominal Muscle Strength and Heading Ability of PS Players. Cahaya Motor FC by 94.6%".